2017
DOI: 10.1016/j.solener.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental analysis of an innovative dual-axis tracking linear Fresnel lenses concentrated solar thermal collector

Abstract: Linear concentrating solar thermal systems offer a promising method for harvesting solar energy. In this paper, a model for a novel linear Fresnel lens collector with dual-axis tracking capability is presented. The main objective is to determine the performance curve of this technology by means of both experiment and theoretical analysis. A mathematical model including the optical model of the concentrator and the heat transfer model of the receiver pipe was developed. This tool was validated with experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(6 citation statements)
references
References 14 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…A model for a new linear Fresnel lens collector with dual-axis tracking capabilities was provided by Perini et al (2017) [44]. The primary goal was to analyze this technology experimentally and theoretically to identify its performance curve.…”
Section: Fresnel Lens Technology In Solar Collectorsmentioning
confidence: 99%
“…A model for a new linear Fresnel lens collector with dual-axis tracking capabilities was provided by Perini et al (2017) [44]. The primary goal was to analyze this technology experimentally and theoretically to identify its performance curve.…”
Section: Fresnel Lens Technology In Solar Collectorsmentioning
confidence: 99%
“…The Fresnel lenses were hosted by an aluminum structure and were maintained normal to sunlight through a 2D tracking device. 10 Experimental results demonstrated that the linearfocusing Fresnel lens with dual-axis tracking could harvest solar energy for all daytime hours. However, such a system takes up considerable land resources and requires large amounts of additional energy consumption to achieve the dual-axis tracking.…”
Section: Introductionmentioning
confidence: 97%
“…The entire system was mounted on a circular orbit for solar azimuth angle tracking. The Fresnel lenses were hosted by an aluminum structure and were maintained normal to sunlight through a 2D tracking device 10 . Experimental results demonstrated that the linear‐focusing Fresnel lens with dual‐axis tracking could harvest solar energy for all daytime hours.…”
Section: Introductionmentioning
confidence: 99%
“…However, other parameters are determinant in the main features of the solar panels, such as: the orientation (tilt), latitude, azimuth, annual irradiance distribution and commercial applications. A more complete physical model making use of an open-source advanced object-oriented Monte Carlo ray tracing program, such as SolTrace [11] or Tonatiuh [12,13], is required for 3-D calculations, to obtain the light distribution along the receiver. The respective results are also shown and discussed along with a comparative analysis between the proposed collectors and the current solar modules of Solarus AB.…”
Section: Introductionmentioning
confidence: 99%